2016
DOI: 10.5348/d05-2016-22-oa-18
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cognitive and behavioral functions in patients with dementia: Practical prognostic models of logarithmic and linear regression

Abstract: Aims: This study provides data on predicting changes in cognitive functions, behavioral independences and disturbances in dementia patients by differential modeling with logarithmic and linear regression. Methods: This longitudinal study included two data analysis groups. Group one: 24 dementia patients for identification of cognitive and behavioral changes over time in group data; group two: 15 dementia patients to ensure correlation of the group data applied to prediction of each individual's degree of cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The present study also found that functional ability in inpatients with schizophrenia could be predicted by logarithmic modelling. We showed that logarithmic modelling can predict functioning of an individual with schizophrenia at discharge over various hospitalisation periods, whereas the predictive model in previous studies (Koyama et al, 2005;Suzuki et al, 2013;Watanabe et al, 2016) was used to assess applicability for all participants in a specific period. Furthermore, the present study showed that logarithmic modelling using the APS score based on brief observation assessments could predict recovery of functional ability for inpatients with schizophrenia during individual rehabilitation Figure 3.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The present study also found that functional ability in inpatients with schizophrenia could be predicted by logarithmic modelling. We showed that logarithmic modelling can predict functioning of an individual with schizophrenia at discharge over various hospitalisation periods, whereas the predictive model in previous studies (Koyama et al, 2005;Suzuki et al, 2013;Watanabe et al, 2016) was used to assess applicability for all participants in a specific period. Furthermore, the present study showed that logarithmic modelling using the APS score based on brief observation assessments could predict recovery of functional ability for inpatients with schizophrenia during individual rehabilitation Figure 3.…”
Section: Discussionmentioning
confidence: 96%
“…For post hoc analyses, significant differences in APS score between the initial assessment and each time point assessment were analysed using the Shirley–Williams multiple comparison test. In addition, to identify the time course of recovery of functional ability in the group data and to construct predictive models, logarithmic (Koyama et al., 2005; Suzuki et al., 2013; Watanabe et al., 2016) and linear regression analyses (Suzuki et al., 2013; Watanabe et al., 2016) were performed with the group data using the following formulae: f(t) = a + b ln (t) and f (t) = a + b (t), where t is the number of days since the beginning of the occupational therapy programme, a is the APS score at the first assessment, and b is the slope of the changes in functional ability at three time points (first, second, and fourth assessments, or first, third, and fourth assessments). We used the APS scores at one week and at one month because functional recovery in schizophrenia requires substantial time (Robinson, Woerner, McMeniman, Mendelowitz, & Bilder, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations